Stellar properties of the host galaxy of an ultraluminous X-ray source in NGC 5252. (22nd January 2020) - Kim, Minjin; López, Kristhell M; Jonker, Peter G; Ho, Luis C; Im, Myungshin
ABSTRACT: An ultraluminous X-ray source (ULX) in NGC 5252 has been known as a strong candidate for an off-nuclear intermediate-mass black hole (IMBH). We present near-infrared imaging data of the ULX obtained with the William Herschel Telescope. Using this data we estimate a stellar mass associated with the ULX of ≈10 7.9 ± 0.1 M_, suggesting that it could be (the remnant of) a dwarf galaxy that is in the process of merging with NGC 5252. Based on a correlation between the mass of the central black hole (BH) and host galaxy, the ULX is powered by a 10 5 M_ BH. Alternatively, if the BH mass is ≈10 6 M_ or larger, the host galaxy of the ULX must have been heavily stripped during the merger. The ULX K s -band luminosity is two orders of magnitude smaller than that expected from an ordinary active galactic nucleus with the observed [O iii ] luminosity, which also suggests the ULX lacks a dusty torus. We discuss how these findings provide suggestive evidence that the ULX is hosting an IMBH.